2‐Deoxy‐D‐glucose impedes T cell–induced apoptosis of keratinocytes in oral lichen planus. Issue 21 (21st October 2021) - Wang, Fang; Zhang, Jing; Zhou, Gang
Abstract: Oral lichen planus (OLP) is a T cell–mediated immunoinflammatory disease. Glycolysis plays an essential role in T‐cell immune responses. Blocking glycolytic pathway in activated T cells represents a therapeutic strategy for restraint of immunologic process in autoimmune disorders. 2‐Deoxy‐D‐glucose (2‐DG) has been widely used to probe into glycolysis in immune cells. This study was aimed to explore the role of glycolysis inhibition by 2‐DG on regulating immune responses of OLP‐derived T cells. We observed that lactic dehydrogenase A (LDHA) expression was elevated in OLP lesions and local T cells. 2‐DG inhibited the expression of LDHA, p‐mTOR, Hif1α and PLD2 in T cells; meanwhile, it decreased proliferation and increased apoptosis of T cells. T cells treated by 2‐DG showed lower LDHA expression and elevated apoptosis, resulting in a reduced apoptotic population of keratinocytes that were co‐cultured with them, which was related to the decreased levels of IFN‐γ in co‐culture system. Rapamycin enhanced the effects of 2‐DG on immune responses between T cells and keratinocytes. Thus, these findings indicated that OLP‐derived T cells might be highly dependent upon high glycolysis for proliferation, and 2‐DG treatment combined with rapamycin might be an option to alleviate T‐cell responses, contributing to reducing apoptosis of keratinocytes.